Falling rate of profit, exploitation of labor and Piketty’s r > g identity in a world of financialization - Mudenda, Lackson D.; Dasgupta, Satyaki (Journal of Income Distribution®, 2025)
This paper studies Marx’s theories of the exploitation of labor and the falling rate of profit alongside Piketty’s identity in the era of financialization. Marx argues that capitalist systems literally exploit labor to extract surplus value, a claim that fans the flames of the critiques of capitalism and contributes to debates about class struggles. Marx also argues that capital accumulation leads to a falling rate of profit, which in modern times can be countered by financialization, as a result guaranteeing the extraction of surplus value. On the other hand, Piketty’s analysis focuses on wealth inequality, proposing that the rate of return on capital outpaces the rate of economic growth (i.e., r > g ), which worsens societal wealth disparities over time, through inheritance and capital income. By synthesizing Marx’s and Piketty’s perspectives within the context of a modern financialized world, this study contributes to ongoing political economy debates on how financial mechanisms sustain the extraction of surplus value. We examine how financial practices influence Marx’s mechanisms of exploitation of labor and the falling rate of profit while also influencing with Piketty’s observations about capital accumulation and inequality. This connection between Marxian theories and contemporary wealth distribution informs debates and enriches discussions on managing inequality in the 21st century.